2017
DOI: 10.3126/jpn.v7i2.18004
|View full text |Cite
|
Sign up to set email alerts
|

A study of ovarian tumors at Kathmandu medical college teaching hospital

Abstract: Background:Ovarian cysts, which present as neoplastic and non-neoplastic lesions, are the most common gynecological cause of hospital admissions. This study was conducted to know the spectrum of ovarian tumors. Materials and Methods: A cross sectional study was carried out among all the ovarian specimens sent for histopathological examination. Results: Germ cell tumour comprises 53.85% followed by Surface epithelial tumours 45.05% and metastatic tumour 1.1%. Among surface epithelial tumours, 82.9% were benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…12 In a study done by Garg et al majority of the tumors were unilateral (95.3%). 9 In our study maximum number of ovarian tumors was noted in 21-30 years age group which concord with the study done by Pradhan et al 14 However, Garg et al, 9 and Jindal et al 26 observed that most common ovarian tumors were in 30-50 years age group.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…12 In a study done by Garg et al majority of the tumors were unilateral (95.3%). 9 In our study maximum number of ovarian tumors was noted in 21-30 years age group which concord with the study done by Pradhan et al 14 However, Garg et al, 9 and Jindal et al 26 observed that most common ovarian tumors were in 30-50 years age group.…”
Section: Resultssupporting
confidence: 87%
“…Yogambal et al, 22 Yasmin et al, 23 and Hassani et al 20 found that the most common benign tumor was serous cyst adenoma which followed by mature cyst teratoma. Ahmed et al 24 and Pradhan et al 14 studies showed benign cystic teratoma was the commonest benign tumor.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar age incidence was also found in ovarian lesions study by Maharjanet al 24 Only 10% of adnexal masses were found to be bilateral. The finding is comparable to study of Pradhaet al 25 and Ranabhat et al 26 There was no significant difference in prevalence of masses in right or left ovary in this study. However, higher prevalence of masses in the right ovary compared to left ovary was found in a study by Bagdeet al 27 and higher prevalence was found in the left ovary by Kaldha et al 28 Adnexal abnormalities in pediatric patient though not common are not rare.…”
Section: Resultssupporting
confidence: 89%
“…Our finding is similar with various studies conducted in different parts of India and Nepal. [6][7][8][9][10][11] Only one case of metastatic tumour is encountered in this study while the rest comprises primary ovarian tumour (99%). Similar observation was seen in the study of Bhagyalakshmi A et al (98.5%).…”
Section: B a C K G R O U N Dmentioning
confidence: 99%